The Spanish Government informative activity during the health emergency induced by coronaviruses, COVID-19 - Ángel Ibáñez Peiró (Universidad Carlos III de Madrid, 2020)
The social impact produced by so-called COVID-19 epidemic all over the world, and its derived effects, is difficult to quantify currently. Although this is not time to come to a final and optimistic conclusion about the Spanish Government response to this health emergency, we can reach a first one, about the way it has established for managing its information policy during the current year first months. For reaching that goal, this paper sets out the legal guidelines the Public Administration must observe in the exercise of the public function of reporting, both in normal situations and in health emergencies like we are living now, caused by the so-called coronavirus. Through these technical-legal frameworks, the analysis of the type of information disseminated, the official spokespersons role and of the Government relation with the media through public financing, we have drawn up a fairly sharp sketch suitable for assessing, with objective parameters, the communicational response produced so far.